Performance of Co-operative Communication Networks using Error Control - Pandit, Archana; Nandi, Arnab (International Journal of Computer Sciences and Engineering, 2014)
Signal transmission in Wireless Networks suffers considerably from much impairment, one of which is channel fading due to multipath propagation. Cooperative Communication is a technique which could be employed to mitigate the effects of channel fading by exploiting Diversity gain achieved via cooperation between nodes and relays. In this scenario, a network containing a sender, a destination and a relay is analyzed. Three cooperative communication schemes which include Amplify and Forward, Decode and Forward and Coded Cooperation are employed with different combining techniques are investigated. The idea behind Cooperative communication is to shows two mobile users communicating with the same destination. Each mobile has one antenna and cannot individually generate spatial diversity. However, it may be possible for one mobile to receive the others transmitting signal, in which case it can forward some version of ï¿½overheardï¿½ information of other users along with its own.